Effect of Vancomycin, Gentamicin and Clindamycin on Cartilage Cells In Vitro - Hermann O. Mayr; Nina Regenbrecht; Moritz Florian Mayr; Bianca Riedel; Melanie L. Hart; Hagen Schmal; Michael Seidenstuecker (Biomedicines, 2023)
Background: The treatment of grafts with vancomycin for ligament reconstruction in knee surgery is the current standard. However, high antibiotic concentrations have chondrotoxic effects. Purpose: To test the chondrotoxicity of clindamycin, gentamicin and vancomycin in comparable concentrations. In vitro and in vivo effective concentrations hugely vary from drug to drug. To allow for comparisons between these three commonly used antibiotics, the concentration ranges frequently used in orthopedic surgical settings were tested. Study Design: Controlled laboratory study. Methods: Human cartilage from 10 specimens was used to isolate chondrocytes. The chondrocytes were treated with clindamycin (1 mg/mL and 0.5 mg/mL), gentamicin (10 mg/mL and 5 mg/mL) or vancomycin (10 mg/mL and 5 mg/mL), at concentrations used for preoperative infection prophylaxis in ligament surgery. Observations were taken over a period of 7 days. A control of untreated chondrocytes was included. To test the chondrotoxicity, a lactate dehydrogenase (LDH) test and a water-soluble tetrazolium salt (WST-1) assay were performed on days 1, 3 and 7. In addition, microscopic examinations were performed after fluorescence staining of the cells at the same time intervals. Results: All samples showed a reasonable vitality of the cartilage cells after 72 h. However, clindamycin and gentamicin both showed higher chondrotoxicity in all investigations compared to vancomycin. After a period of 7 days, only chondrocytes treated with vancomycin showed reasonable vitality. Conclusions: The preoperative treatment of ligament grafts with vancomycin is the most reasonable method for infection prophylaxis, in accordance with the current study results regarding chondrotoxicity; however, clindamycin and gentamicin cover a wider anti-bacterial spectrum. Clinical Relevance: The prophylactic antibiotic treatment of ligament grafts at concentrations of 5 mg/mL or 10 mg/mL vancomycin is justifiable and reasonable. In specific cases, even the use of gentamicin and clindamycin is appropriate.